Association of the inflammation-related proteome with dementia development at older age: results from a large, prospective, population-based cohort study - Trares, Kira; Bhardwaj, Megha; Perna, Laura; Stocker, Hannah; Petrera, Agnese; Hauck, Stefanie M.; Beyreuther, Konrad; Brenner, Hermann; Schöttker, Ben (Alzheimer's research & therapy, 2022)
Chronic inflammation is a central feature of several forms of dementia. However, few details on the associations of blood-based inflammation-related proteins with dementia incidence have been explored yet.